Design elements of houses among disabled community: the satisfaction and the preferences - Ab Rahman, Syakir Amir; Samsudin, Nasriah; Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati (Malaysian Institute of Planners, 2018)
Home ownership creates stability and improves the quality of life of the disabled communities. As Malaysia approaches the developed status and the high – income economy by 2020, the housing industry needs to be adaptive to the demands for special groups. Universal homes incorporate universal design principles, resulting in a living environment that can be adapted to virtually any user’s long term comfort, safety and ease. The aim of this paper is to study on the preferences and level of satisfaction on design factor in owning residential property among the disabled community in Kuala Lumpur and Selangor. A questionnaire survey was conducted on a sample of 800 respondents. The respondents were selected from the disabled community, focusing on two categories of disabilities, physical and visual impairment. The outcome of this study shows that disabled people prefer houses which are complete with design that accommodates residents’ physical limitations. For design elements of their residential property, this study found that the disabled people are satisfied with the provision of ramp to access into the building, while their satisfaction on design for the low physical effort scored at seventh place. The study concludes with two housing recommendations: to provide at least the minimum requirement of universal design in all upcoming projects and to provide home modification scheme.